Smart Spaces and Next Generation Wired/Wireless Networking Third Conference on Smart Spaces, ruSMART 2010, and 10th International Conference, NEW2AN 2010, St. Petersburg, Russia, August 23-25, 2010. Proceedings - Balandin, Sergey; Dunaytsev, Roman; Koucheryavy, Yevgeni; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 10th International Conference on Next Generation Teletraffic and Wired/Wireless Advanced Networking, NEW2AN 2010, held in conjunction with the Third Conference on Smart Spaces, ruSMART 2009 in St. Petersburg, Russia, in August 2010. The 27 revised NEW2AN full papers are organized in topical sections on performance evaluation; performance modeling; delay-/disruption-tolerant networking and overlay systems; integrated wireless networks; resource management; and multimedia communications. The 14 revised ruSMART full papers are about smart spaces use cases; smart-M3 platform; and smart spaces solutions.
ruSMART -- Extending Context Spaces Theory by Proactive Adaptation -- Context-Awareness Enabling New Business Models in Smart Spaces -- A Middleware Architecture for Safety Critical Ambient Intelligence Applications -- Ranking Algorithm by Contacts Priority for Social Communication Systems -- CrysP: Multi-Faceted Activity-Infused Presence in Emerging Social Networks -- Multichannel System of Audio-Visual Support of Remote Mobile Participant at E-Meeting -- On-the-Fly Ontology Matching in Smart Spaces: A Multi-model Approach -- Access Control in Personal Localized Semantic Information Spaces -- Integration of an Answer Set Engine to Smart-M3 -- A Video Monitoring Model with a Distributed Camera System for the Smart Space -- Physical Approach in Smart Homes -- SMEO: A Platform for Smart Classrooms with Enhanced Information Access and Operations Automation -- Creative Approach to the Design and Prototyping of Experimental Smart Spaces, Case Studies from the Interactive Environments Minor -- Event Recognition via Energy Efficient Voting for Wireless Sensor Networks -- NEW2AN -- Evaluation of Multi-service CDMA Networks with Soft Blocking -- Design of MPLS over DWDM Architecture for Unicast and Anycast Flows -- Comparative Analysis of Sleep Mode Control Algorithms for Contemporary Metropolitan Area Wireless Networks -- Determining Normalized Measure of Dispersion for Evaluating the Performance of IEEE 802.11 -- Development of a System to Promote Eco-Driving and Safe-Driving -- Oligopoly Game Modeling for Cognitive Radio Environments -- Reducing the Number of States for Markovian Model of Optical Slotted Ring Network -- Performance Modelling of Automatic Identification System with Extended Field of View -- Performance Measures Computation for a Single Link Loss Network with Unicast and Multicast Traffics -- Realization of a Method of Matrix-Geometric Progression -- Mobility Pattern Based Routing Algorithm for Delay/Disruption Tolerant Networks -- Heuristic Congestion Control for Message Deletion in Delay Tolerant Network -- The FDPOO: A Flexible Delivering Platform with at-One-time and On-time Guarantees in Opportunistic Networks -- A Distributed Telematics Peer-to-Peer (D-TP2P) Networking System for Service Discovery -- Empirical Predictor of TCP Throughput on a Multihop Wireless Path -- A Framework for Connectivity in Inter-working Multi-hop Wireless Networks -- Practical Vertical Handover Mechanisms between Satellite and Terrestrial Networks -- Geo-aware Handover of Mission Agents Using Opportunistic Communication in VANET -- Comparison and Evaluation of the Most Efficient Mobility Management Protocols for Integrated Wireless Networks -- Functional Model and Service Scenarios for QoS Enabled Mobile VoIP Service -- Heuristic Approaches to the Multi-objective Network Design and Optimization for Wireless Data Networks -- Call Admission Control in Single and Two-Tier Cellular Networks -- Joint Admission Control and Resource Allocation for Multiuser Loading in LTE Networks -- Data Traffic Scheduling Algorithm for Multiuser MIMO-OFDM System with the Throughput Maximization -- Scalable Video Coding Based on Three-Dimensional Discrete Pseudo Cosine Transform -- NTRULO: A Tunneling Architecture for Multimedia Conferencing over IP -- Seamless Streaming Service Session Migration Support Architecture for Heterogeneous Devices.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information systems; Information Systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Software Engineering; Algorithm Analysis and Problem Complexity; Computers and Society; Management of Computing and Information Systems